From Migrant Identity to Migration Industry: 'The changing conditions of transnational migration' - Ninna Nyberg Sørensen (Nordic Journal of Migration Research, 2018)
In this article, I reflect on changes in the conditions of transnational mobility over the past 25 years. Drawing on continuous engagement with Dominican migrants in sending, transit, destination and return situations, I argue that increasingly strict migration control measures during this period have profoundly altered the existential option of living lives across borders. I specifically address changes in the right to move and settle, the absence of avenues for regular migration and the concomitant rise in high-risk irregular migration. Examples include the risk to life, safety and investments during journeys, the risk of exploitation in both transit and destination countries and the risks resulting from being subject to deportation and removal from family and community. I argue that the by now well-established tradition of transnational migration research, in particular the multi-local focus on the social relations that facilitate migration, can be fruitfully extended by paying equal attention to structural factors that restrict mobility.